Perovskite solar cell adopting low-melting-point alloy back electrode and preparation method of perovskite solar cell
Preparation of low-melting point alloy In-xSn-yBi back electrode by hot pressing method, solving the problems of high cost and low stability of precious metal back electrodes in perovskite solar cells, and achieving high efficiency, high stability and low cost pertitanium Rapid industrial production of mineral solar cells.
Patent Information
- Application Number
- CN202411532678.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
Among the existing perovskite solar cells, the precious metal Au and Ag back electrodes have high cost and complex preparation processes. The stability of the battery is reduced due to ion migration, making it difficult to achieve fast industrial production with low cost, high efficiency and high stability.
The metal back electrode of perovskite solar cell was prepared by using low melting point alloy In-xSn-yBi to closely fit on the carrier transport layer by hot pressing, and the alloy composition was adjusted to match different energy level structures and temperature tolerances. .
It realizes the high repeatability and high photoelectric conversion efficiency of perovskite solar cells, reduces the production cost and equipment requirements, and is suitable for the large-scale production of perovskite solar cells.
Smart Images

Figure CN119486561A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photovoltaic materials and devices, and in particular relates to a method for rapidly preparing a low-melting-point alloy back electrode and a perovskite solar cell thereof. Background Art
[0002] The photoelectric conversion efficiency of perovskite solar cells (PSCs) has developed rapidly, and the conversion efficiency of single-cell PSCs has exceeded 26%. In recent years, PSCs have attracted widespread attention from the industry due to their high efficiency, simple preparation process, and low cost. In PSCs, the back electrode plays an important role in collecting carriers, connecting external circuits, and protecting other functional layers of the battery. Currently, the back electrodes of high-efficiency PSCs mostly use Au or Ag electrodes prepared by vacuum thermal evaporation. However, the cost of precious metal Au and Ag materials is high, and vacuum thermal evaporation is heavily dependent on precision equipment, the process flow is complex, and it is time-consuming and energy-consuming, which is not conducive to the rapid and low-cost industrial production of PSCs. In addition, ion migration occurs during the operation of PSCs. On the one hand, the halogen ions (I - On the other hand, metal ions migrate to the perovskite layer and induce the decomposition of perovskite. Ion migration and reaction significantly reduce the stability of PSCs. In addition to metal back electrodes, carbon electrodes are another type of back electrode for preparing low-cost PSCs. Due to the poor conductivity of carbon electrodes and the loose interface contact with the functional layer of PSCs, the photoelectric conversion efficiency of PSCs using carbon back electrodes is currently significantly lower than that of batteries using Au and Ag back electrodes. Therefore, developing a metal back electrode with low cost, simple preparation process and good stability to prepare high-efficiency PSCs is of great significance to promote the industrialization and application of perovskite photovoltaics.
[0003] Low-melting-point alloys are a type of metal material with a melting temperature below 200°C, which exhibits good fluidity at temperatures above its melting point. Among them, the melting point of eutectic gallium-indium (EGaIn) alloy is lower than room temperature, and it is called liquid metal because it is liquid at room temperature. At room temperature, liquid metal electrodes can be transferred to a substrate or other functional layer by brushing, printing, screen printing, etc., without the need for expensive equipment and a vacuum environment. In 2023, Ji-Hye Kim et al. prepared perovskite solar cells by spreading EGaIn liquid metal on an electron transport layer as a back electrode by a template coating method, and the cell achieved a photoelectric conversion efficiency of 8.9% (Adv. Funct. Mater. 2024, 34, 2311597). However, the melting point of EGaIn is lower than room temperature, and the liquid metal tends to spheroidize spontaneously due to its extremely large surface tension. Therefore, under the thermal effect generated by continuous illumination, the EGaIn back electrode of the perovskite solar cell is at risk of melting, shrinking and failing. Therefore, it is very necessary to invent a low-melting-point alloy back electrode with a melting point higher than room temperature and a preparation method thereof, so as to realize the rapid and large-scale preparation of low-cost, high-efficiency and high-stability perovskite solar cells. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, an object of the present invention is to provide a method for preparing a low melting point alloy back electrode and its application in perovskite solar cells.
[0005] The present invention utilizes the good fluidity and atomic diffusivity of low-melting-point alloys in a molten state to achieve close fitting of alloy foil on the carrier transport layer under hot pressing conditions, and serves as the metal back electrode of the perovskite solar cell. By adjusting the alloy composition, the work function and melting point of the alloy electrode can be effectively regulated, so that this type of alloy back electrode can match the perovskite light absorption layer and carrier transport layer with different energy level structures and temperature tolerances, thereby improving the flexibility and diversity of material selection and structural design of each functional layer of PSCs. The preparation process of the low-melting-point alloy back electrode is simple and fast, can be completed under low temperature conditions, and does not require vacuum conditions and precision equipment. The use of this hot pressing method to prepare the back electrode can greatly improve the preparation efficiency of PSCs, reduce the production cost, and is conducive to the large-scale production of PSCs. The prepared PSCs have high repeatability and high photoelectric conversion efficiency.
[0006] The back electrode described in the present invention is a low melting point alloy back electrode prepared by hot pressing.
[0007] The perovskite solar cell described in the present invention comprises a transparent conductive substrate, a carrier transport layer 1, a perovskite light absorption layer, a carrier transport layer 2 and an alloy back electrode.
[0008] Preferably, the transparent conductive substrate is FTO, ITO conductive glass or ITO / PEN, ITO / PET flexible substrate.
[0009] Preferably, the perovskite light absorbing layer is Cs 1-x-y FA x MA y PbI 3 Organic-inorganic perovskite (where 0≤x≤1, 0≤y≤1, x+y≤1; FA is NH4-carbazide 2 CH=NH + ,MA is methylamino CH 3 NH + ) or CsPbI 2 Br all-inorganic perovskite.
[0010] To achieve the purpose of the present invention, the following technical solutions are adopted.
[0011] The present invention provides a method for preparing a low melting point alloy back electrode, comprising the following steps:
[0012] A method for preparing a perovskite solar cell using a low melting point alloy back electrode comprises the following steps:
[0013] (1) depositing a carrier transport layer 1, a perovskite light absorption layer, and a carrier transport layer 2 on a transparent conductive substrate in sequence to obtain a perovskite electrode;
[0014] (2) laying a low melting point alloy foil flat on the carrier transport layer 2 of the perovskite electrode obtained in step (1);
[0015] (3) placing a pressure mold on the alloy foil / perovskite electrode formed in step (2) to generate or apply a certain pressure;
[0016] (4) heating the alloy foil / perovskite electrode in step (3) and keeping it warm for a period of time under continuous pressure, so that the alloy foil electrode is attached to the carrier transport layer 2;
[0017] (5) Cooling the device described in step (4), removing the mold, and obtaining a perovskite solar cell using a low-melting-point alloy back electrode.
[0018] Furthermore, the material of the low melting point alloy foil in step (2) is In-aSn-bBi, and the melting point selection range is 40-150°C, wherein a and b are the mass percentages of Sn and Bi in the alloy respectively, and the remainder is In; wherein 0≤a≤65, 0≤b≤90, a+b≤100.
[0019] Further preferably, the low melting point alloy in step (2) is one of In-16.5Sn-32.5Bi, In-33Bi, and In-53Sn, and the melting points thereof are 60.5°C, 70°C, and 119°C, respectively.
[0020] More preferably, the low melting point alloy foil has a thickness of 0.2 to 50 μm, preferably 10 μm.
[0021] Furthermore, the pressure applied to the alloy foil / perovskite electrode in step (3) is provided by the stainless steel mold itself or by an external mechanical pressurizing device.
[0022] Furthermore, the pressure in step (3) is 0.05-0.5 MPa.
[0023] Further preferably, the pressure in step (3) is provided by a stainless steel pressure mold of a certain mass, and the pressure is 0.2 MPa.
[0024] Furthermore, the heating temperature in step (4) is 5-20° C. above the melting point of the alloy, and the insulation time is 1-20 minutes.
[0025] Further preferably, the heating temperature in step (4) is 15° C. above the melting point of the alloy, and the holding time is 10 minutes.
[0026] Furthermore, the cooling method in step (5) is natural cooling.
[0027] The present invention provides a low melting point alloy back electrode prepared by the above preparation method. That is, the back electrode of the present invention is obtained by laminating a low melting point alloy foil on the carrier transport layer 2 of the perovskite solar cell by hot pressing.
[0028] The present invention provides a positive structure (attached Figure 2a ) or inverted structure (with Figure 2b ) perovskite solar cell, comprising a transparent conductive substrate, a carrier transport layer 1, a perovskite light absorbing layer, a carrier transport layer 2 and a metal back electrode stacked in sequence, wherein the metal back electrode is prepared from a low melting point alloy by hot pressing.
[0029] The present invention provides a method for preparing a perovskite solar cell with an upright structure (including a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a low melting point alloy back electrode stacked in sequence), comprising the following steps:
[0030] (1) using a semiconductor process to clean the conductive substrate, blow dry and perform ultraviolet-ozone treatment, depositing an electron transport material on the conductive substrate, and annealing to obtain an electron transport layer;
[0031] (2) depositing a perovskite light absorbing layer on the electron transport layer;
[0032] (3) depositing a hole transport layer on the perovskite light absorbing layer;
[0033] (4) A low melting point alloy back electrode is prepared on the hole transport layer by a hot pressing method to obtain the upright structure perovskite solar cell.
[0034] Furthermore, the electron transport layer in step (1) is SnO 2 、TiO 2 or at least one of ZnO thin films;
[0035] Furthermore, the electron transport layer deposition method in step (1) is one of spin coating, atomic layer deposition and chemical bath deposition.
[0036] Further preferably, the electron transport layer in step (1) is SnO 2 The deposition method is spin coating, the annealing temperature is 180°C, and the annealing time is 20 minutes.
[0037] Furthermore, the perovskite light absorbing layer in step (2) is Cs 1-x-y FA x MA y PbI 3 Organic-inorganic perovskite or CsPbI 2 Br all-inorganic perovskite, thickness is 300-800nm.
[0038] Further preferably, the perovskite in step (2) is FAPbI 3 , with a thickness of approximately 720nm.
[0039] Furthermore, the hole transport layer in step (3) is Spiro-OMeTAD or NiO x At least one of.
[0040] Furthermore, the hole transport layer deposition method in step (3) is spin coating or scraping coating.
[0041] Further preferably, the hole transport layer in step (3) is a Spiro-OMeTAD layer prepared by spin coating and has a thickness of 150 nm.
[0042] The present invention provides a method for preparing an inverted structure perovskite solar cell (including a transparent conductive substrate, a hole transport layer, a perovskite light absorption layer, an electron transport layer and a low melting point alloy back electrode stacked in sequence), comprising the following steps:
[0043] (1) using a semiconductor process to clean the conductive substrate, blow dry and perform ultraviolet-ozone treatment, deposit a hole transport material on the conductive substrate, and perform annealing to obtain a hole transport layer;
[0044] (2) depositing a perovskite light absorbing layer on the hole transport layer;
[0045] (3) depositing an electron transport layer on the perovskite light absorbing layer;
[0046] (4) A low melting point alloy back electrode is prepared on the electron transport layer by a hot pressing method to obtain the inverted structure perovskite solar cell.
[0047] Furthermore, the hole transport layer in step (1) is NiO x , [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine (PTAA), PEDOT:PSS.
[0048] Furthermore, the hole transport layer deposition method in step (1) is spin coating or scraping coating.
[0049] Further preferably, the hole transport layer in step (1) is NiO x , the thickness is about 50nm, the annealing temperature is 120℃, and the annealing time is 10 minutes.
[0050] Furthermore, the perovskite light absorbing layer in step (2) is Cs 1-x-y FA x MA y PbI 3 Organic-inorganic perovskite or CsPbI 2 Br all-inorganic perovskite, thickness is 300-800nm.
[0051] Further preferably, the perovskite in step (2) is Cs 0.05 FA 0.75 MA 0.2 PbI 3 , thickness is 680nm.
[0052] Furthermore, the electron transport layer in step (3) is PC 61 At least one of BM and C60.
[0053] Furthermore, the electron transport layer deposition method in step (3) is spin coating or thermal evaporation.
[0054] Furthermore, the electron transport layer in step (3) is PC 61 When BM or C60 is used, a BCP (2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline) layer with a thickness of about 10 nm is spin-coated thereon.
[0055] Further preferably, the electron transport layer in step (3) is BC deposited by spin coating. 61 PM, thickness is about 100nm.
[0056] The present invention uses a low melting point In-xSn-yBi alloy foil as an electrode material, and adheres it to the carrier transport layer 2 of a perovskite solar cell by hot pressing, thereby obtaining a back electrode of a perovskite solar cell. During the heating process, when the temperature is higher than the melting point of the alloy, the alloy melts and exhibits good fluidity and atomic diffusion ability; under the action of a mold or a certain pressure, the molten alloy flows and diffuses toward the carrier transport layer 2, achieving a close fit with the carrier transport layer at the atomic level, which ensures barrier-free carrier transmission at the transport layer / back electrode interface from the perspective of physical contact. More importantly, good matching of the work functions of each functional layer in a solar cell is the most critical prerequisite for achieving efficient transfer of interface carriers. The work function of the In-xSn-yBi alloy back electrode can be flexibly adjusted by changing the alloy composition, which provides great convenience for the selection of each functional layer of PSCs and the diversity of battery structure design. The excellent matching of the work function of the back electrode and the carrier transport layer ensures the rapid transfer of carriers at the transport layer / back electrode interface from an electrical perspective. In addition, the shuttle diffusion of metal ions and perovskite halide ions is an important factor inducing the instability of perovskite solar cells. In-xSn-yBi is an easily oxidized material. By exposing it to air on the surface of the alloy foil to form a dense oxide layer of nanometer thickness, it can effectively block the shuttle diffusion of ions and improve the stability of the battery. In one embodiment of the present invention, a perovskite solar cell prepared with an In-33Bi alloy back electrode can achieve a photoelectric conversion efficiency of more than 18%.
[0057] The present invention utilizes the characteristics of In-xSn-yBi low melting point alloy that is easy to melt and exhibits good fluidity under melting conditions, and makes it closely fit on the carrier transport layer through hot pressing to become the back electrode of the perovskite solar cell. The method has the advantages of simple process, low temperature, low cost, fast, easy to repeat, etc. The use of the back electrode and its preparation technology can greatly reduce the preparation cost of the perovskite solar cell, reduce equipment requirements, and improve the efficiency of battery preparation, while ensuring the high photoelectric conversion efficiency and excellent stability of the perovskite solar cell, which is conducive to the industrial production of perovskite solar cells.
[0058] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0059] (1) In the In-xSn-yBi low-melting-point alloy back electrode and its preparation method provided by the present invention, the work function and melting point of the In-xSn-yBi alloy are flexibly adjustable, and can be optimized and matched with the perovskite light-absorbing layer and carrier transport layer with different work functions, which greatly facilitates the selection of various functional layers of perovskite solar cells and the diversity of battery structure design.
[0060] (2) In the In-xSn-yBi low melting point alloy back electrode and its preparation method provided by the present invention, the price of In-xSn-yBi alloy is about 2-3 yuan / gram, which is only 1 / 3 of the most commonly used metal back electrode material Ag (~7 yuan / gram) for perovskite solar cells and 1 / 10-1 / 20 of Au (250-600 yuan / gram). Under the condition that metal electrode materials account for about 30-40% of the total cost of perovskite solar cells, the low-priced In-xSn-yBi as the back electrode can greatly reduce the material cost of perovskite solar cells.
[0061] (3) In the In-xSn-yBi low-melting-point alloy back electrode and its preparation method provided by the present invention, the hot pressing process only takes 1-10 minutes, which greatly shortens the preparation time of the back electrode and is conducive to the continuous and rapid production of perovskite solar cells.
[0062] (4) In the In-xSn-yBi low-melting-point alloy back electrode and its preparation method provided by the present invention, the back electrode preparation temperature is low (<150°C) and no precision equipment is required. Compared with the traditional thermal evaporation high-melting-point metal (Ag, Ag) back electrode, the equipment cost and energy cost of perovskite solar cell production can be greatly reduced.
[0063] (5) In the In-xSn-yBi low-melting-point alloy back electrode and its preparation method provided by the present invention, the In-xSn-yBi alloy has excellent flexibility and tailorability, and the electrode preparation temperature is low, which is suitable for the roll-to-roll method to prepare low-temperature, flexible perovskite solar cells.
[0064] (6) The process provided by the present invention is simple, repeatable and low-cost, providing a new feasibility for preparing high-efficiency perovskite solar cells. The low-melting-point alloy back electrode preparation technology of the present invention has broad application prospects in many fields such as other photovoltaic devices, photoelectric detection, LED, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 It is a schematic diagram of the structure of a perovskite solar cell prepared by using a low melting point alloy in the present invention.
[0066] Figure 2a This is a schematic diagram of the structure of an inverted perovskite solar cell made of a low-melting-point alloy.
[0067] Figure 2b This is a schematic diagram of the structure of an inverted perovskite solar cell made of a low-melting-point alloy.
[0068] Figure 3 This is a photo of the perovskite solar cell based on In-53Sn alloy back electrode prepared in Example 1.
[0069] Figure 4 This is the JV curve of the perovskite solar cell prepared in Example 1.
[0070] Figure 5 This is a photo of a perovskite solar cell based on an In-53Sn alloy back electrode prepared by the hot pressing method in Example 2.
[0071] Figure 6 This is the JV curve of the perovskite solar cell prepared in Example 2.
[0072] Figure 7 This is the JV curve of the perovskite solar cell prepared in Example 3.
[0073] Figure 8 This is the JV curve of the perovskite solar cell prepared in Example 4.
[0074] Fig. 9 This is the JV curve of the perovskite solar cell prepared in Example 5.
[0075] Fig.10 This is the JV curve of the perovskite solar cell prepared in Example 6.
[0076] Fig.11 This is the JV curve of the perovskite solar cell prepared in Example 7.
[0077] Fig.12 This is the JV curve of the flexible perovskite solar cell prepared in Example 8. Specific implementation methods
[0079] The specific implementation of the present invention is further described below in conjunction with the examples and drawings, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0080] Example 1
[0081] (1) Cleaning of ITO conductive glass:
[0082] The ITO transparent conductive glass was ultrasonically cleaned with detergent solution, deionized water, acetone, isopropanol and deionized water for 20 minutes in sequence, and the cleaned ITO glass substrate was stored in ethanol solution for later use. It was dried with nitrogen before use and then placed in a UV-ozone cleaning machine for 20 minutes.
[0083] (2) Preparation of electron transport layer:
[0084] In this embodiment, SnO 2 Electron transport layer. Commercial SnO 2 Colloid (15wt.%, AlfaAesar) as SnO 2 : deionized water = 1:3 (V / V) ratio dilution, ultrasonic dispersion for 15 minutes, and then filtered with a 0.22μm TPFE aqueous phase filter membrane to obtain SnO 2 Dispersion liquid. Use a homogenizer to mix SnO 2 The dispersion was spin-coated on a clean ITO substrate at 4000 rpm for 30 s and then annealed on a hot plate at 180 °C for 20 min to obtain SnO 2 Electron transport layer: The thickness of the electron transport layer is about 50 nm.
[0085] (3) Preparation of perovskite light absorbing layer:
[0086] This embodiment uses FAPbI 3 Perovskite light-absorbing material. First, 572.3 mg of lead iodide (PbI 2 ), 201.2 mg of formamidine iodide (FAI), 27.6 mg of methyl ammonium chloride (MACl) powder, dissolved in dimethylformamide (DMF): dimethyl sulfoxide (DMSO) = 520 μL: 130 μL mixed solvent, magnetically stirred for 12 hours and filtered with a 0.22 μm TPFE organic phase filter to obtain a perovskite precursor solution. Then, the perovskite precursor solution was spin-coated on SnO at 4000 rpm-30 s. 2 On the electron transport layer, 750 μL of anti-solvent ether was added dropwise during the last 10 seconds of the spin coating process. After the spin coating, the FAPbI was obtained by annealing at 150°C for 20 minutes in an air atmosphere with a relative humidity (RH) of 30%. 3 Perovskite light-absorbing layer, the thickness of the perovskite layer is about 720nm.
[0087] (4) Preparation of hole transport layer:
[0088] In this embodiment, NiO x Hole transport layer. Weigh 20 mg NiO xNanoparticle powder (~5nm) was added to 1ml of isopropanol and dispersed evenly by ultrasonication for 10 minutes. NiO x The dispersion was spin-coated on the perovskite light-absorbing layer and annealed at 100°C for 10 minutes to obtain NiO x The hole transport layer has a thickness of about 80 nm.
[0089] (5) Preparation of alloy back electrode:
[0090] In this embodiment, In-53Sn alloy foil with a melting point of 119°C is used as the electrode material, and the thickness of the alloy foil is 500nm. The flat alloy foil is laid flat on the Spiro-OMeTAD hole transport layer, and the above battery is heated to 135°C, kept warm for 20 minutes, and then naturally cooled to obtain a perovskite solar cell using an In-53Sn alloy back electrode. The battery photo is shown in FIG. Figure 3 As shown in the photo, it can be seen that the back electrode obtained by directly laying the alloy foil flat on the carrier transport layer 2 and heating it is uneven, with a large number of pores under the film, and the low-melting-point alloy shrinks in some areas and becomes granular. This shows that under the condition of no pressure, the low-melting-point alloy cannot fit tightly with the transport layer due to the influence of surface tension.
[0091] (6) Testing:
[0092] At AM1.5 standard, 100mW cm -2 The photoelectric performance of perovskite solar cells was tested under a light intensity of , and the effective illumination area was 0.12cm 2 The obtained photocurrent density-photovoltage (JV) curve is as follows Figure 4 The photoelectric performance parameters of the cell are: open circuit voltage is 0.60V, short circuit photocurrent density is 10.81mA·cm -2 , the filling factor is 0.42, and the photoelectric conversion efficiency is 2.76%. This shows that without applying pressure, the efficiency of perovskite solar cells prepared with In-Sn binary low-melting-point alloy back electrodes is very low, and the cell efficiency repeatability is extremely poor. Most of the cells do not work or the efficiency is less than 1%.
[0093] Example 2
[0094] (1) Cleaning of ITO conductive glass: Same as Example 1.
[0095] (2) Preparation of electron transport layer: same as in Example 1.
[0096] (3) Preparation of perovskite light absorbing layer: same as in Example 1.
[0097] (4) Preparation of hole transport layer: same as in Example 1.
[0098] (5) Preparation of alloy back electrode:
[0099] The difference is that a certain pressure is applied to the alloy foil electrode in this embodiment. The specific operation is to press a stainless steel mold with a weight of 1 kg, which has been treated with carbon layer wettability, onto the electrode (area 2.25 cm 2 ) on the electrode, forming a pressure of 0.44MPa on the electrode and maintaining the pressure during heating and cooling. After cooling, the mold was removed, and a photo of a perovskite solar cell using an In-53Sn alloy back electrode was prepared. Figure 5 As shown in the figure, under the action of pressure and heating, the alloy electrode is flat, uniform and tightly attached to the carrier transport layer. This shows that the hot pressing method can prepare a low-melting-point alloy back electrode on the carrier transport layer, which is conducive to the rapid transfer of interface carriers.
[0100] (6) Testing:
[0101] The test conditions are the same as in Example 1. The results are as follows Figure 6 The photovoltaic performance parameters of the cell are: open circuit voltage 0.77V, short circuit photocurrent density 19.50mA·cm -2 , the filling factor is 0.49, the photoelectric conversion efficiency is 7.39%, and the cell efficiency shows good repeatability. This shows that the In-Sn binary low melting point alloy back electrode prepared by the hot pressing method of the present invention can be used to prepare a positive structure perovskite solar cell.
[0102] Example 3
[0103] (1) Cleaning of ITO conductive glass: Same as Example 1.
[0104] (2) Preparation of electron transport layer: same as in Example 1.
[0105] (3) Preparation of perovskite light absorbing layer:
[0106] In this embodiment, CsPbI 2 Br as the perovskite light-absorbing layer. Weigh 0.337g of cesium iodide (CsI), 0.313g of lead iodide (PbI 2 ), 0.239 g lead bromide (PbBr 2 ) and 0.025 g MACl were dissolved in 1 mL of DMF:DMSO mixed solvent (volume ratio 2:3), and magnetically stirred for 12 hours and filtered through a 0.22 μm TPFE organic phase filter to obtain a perovskite precursor solution. The perovskite precursor solution was then spin-coated on SnO at 4000 rpm for 30 s. 2 On the electron transport layer, 750 μL of anti-solvent isopropanol was added dropwise at the last 10 seconds of the spin coating process. After the spin coating was completed, the film was annealed at 185° C. for 10 minutes to obtain a perovskite light absorption layer film.
[0107] (4) Preparation of hole transport layer: same as in Example 1.
[0108] (5) Preparation of alloy back electrode:
[0109] This embodiment uses Sn-43Bi alloy foil with a melting point of 139°C as the electrode material, and the thickness of the alloy foil is 50 μm. The preparation steps are the same as those in Example 2, except that the pressure applied by the mold is 0.5 MPa, the heating temperature is 159°C, and the holding time is 20 minutes.
[0110] (6) Testing:
[0111] The test conditions are the same as in Example 1. The results are as follows Figure 7 The photoelectric performance parameters of the battery are as follows: open circuit voltage 0.64V, short circuit photocurrent density 15.14mA·cm -2 , the filling factor is 0.64, the photoelectric conversion efficiency is 5.92%, and the cell efficiency shows good repeatability. This shows that the hot-pressed Sn-Bi binary low-melting-point alloy back electrode of the present invention can be used to prepare a positive structure perovskite solar cell.
[0112] Example 4
[0113] (1) Cleaning of FTO conductive glass:
[0114] This embodiment uses an FTO conductive glass substrate, and the cleaning method is the same as that of Embodiment 1.
[0115] (2) Preparation of electron transport layer:
[0116] In this embodiment, dense TiO 2 Electron transport layer. 0.5 mL of acetic acid was added to 4 mL of n-butanol / isopropanol (v:v=2:1) solution and mixed evenly. Then 0.5 mL of n-butyl titanate was added thereto and shaken for 1 minute to mix evenly. The mixed solution was aged for 2 days to obtain TiO 2 Sol. TiO 2 The sol was spin-coated on a clean FTO substrate and then annealed at 500 °C for 15 min to obtain TiO 2 Electron transport layer.
[0117] (3) Preparation of perovskite light absorbing layer: same as in Example 1.
[0118] (4) Preparation of hole transport layer:
[0119] In a nitrogen glove box, 90 mg of Spiro-OMeTAD powder was weighed and dissolved in 1 mL of chlorobenzene solution. After shaking until clear, 35 μL of t-BP (4-butylpyridine), 23 μL of Li-TFSI (bis(trifluoromethanesulfonyl)imide lithium salt, 520 mg / mL, dissolved in acetonitrile) and 15 μL of FK209 (cobalt-based bis(trifluoromethanesulfonyl)imide lithium salt, 375 mg / mL, dissolved in acetonitrile) were added. Stir overnight for use to obtain a hole transport layer solution. The hole transport layer solution was then spin-coated on the perovskite film at 3000 rpm-30 s to obtain a Spiro-OMeTAD hole transport layer with a thickness of about 150 nm.
[0120] (5) Preparation of alloy back electrode:
[0121] This embodiment uses In-21.3Bi alloy foil with a melting point of 72°C as the electrode material, and the thickness of the alloy foil is 12 μm. The preparation steps are the same as those in Example 2, except that the pressure applied by the mold is 0.1 MPa, the heating temperature is 85°C, and the holding time is 2 minutes.
[0122] (6) Testing:
[0123] The test conditions are the same as those in Example 1. The obtained JV curve is as follows Figure 8 The photovoltaic performance parameters of the cell are: open circuit voltage 1.05V, short circuit photocurrent density 19.38mA·cm -2 , the filling factor is 0.63, the photoelectric conversion efficiency is 12.79%, and the cell efficiency shows good repeatability. This shows that the In-Bi binary low melting point alloy back electrode prepared by the hot pressing method of the present invention can be used to prepare a positive structure perovskite solar cell.
[0124] Example 5
[0125] (1) Cleaning of ITO conductive glass: Same as Example 1.
[0126] (2) Preparation of hole transport layer:
[0127] In this embodiment, PEDOT:PSS is used as a hole transport layer. A 15wt.% PEDOT:PSS dispersion is diluted according to PEDOT:PSS:methanol=1:4 (V / V), and then ultrasonically dispersed for 15 minutes. The diluted PEDOT:PSS dispersion is spin-coated on a clean ITO glass substrate at 4000rmp-30s using a homogenizer, and then annealed on a hot plate at 120°C for 10 minutes to obtain a PEDOT:PSS hole transport layer with a thickness of about 50nm.
[0128] (3) Preparation of perovskite light absorbing layer:
[0129] This embodiment uses MAPbI 3 The perovskite film is used as the light-absorbing layer. The specific preparation steps are as follows: 0.8298 g of lead iodide (PbI 2 ), 0.2861g of methylamine iodide (MAI) powder was dissolved in a mixed solvent of dimethylformamide (DMF): dimethyl sulfoxide (DMSO) = 900μL: 100μL (the volume ratio of DMF and DMSO was 9:1), and then magnetically stirred for 12 hours and filtered for use. Before use, the solution was filtered with a 0.22μm organic phase filter to obtain a perovskite precursor solution. Then, the perovskite precursor solution was spin-coated on the hole transport layer at 4000rpm-30s, and 70μL of anti-solvent chlorobenzene was added in the last 20s. After the spin coating was completed, the perovskite film was annealed at 100℃ for 10 minutes under 30%RH to obtain a perovskite film with a thickness of about 550nm.
[0130] (4) Preparation of electron transport layer:
[0131] This embodiment uses PC 61 BM is used as the electron transport layer. 20 mg of PC was weighed in a nitrogen glove box. 61 BM powder was dispersed in 1 mL of chlorobenzene solution and stirred overnight to obtain PC 61 BM electron transport layer dispersion. Finally, the electron transport layer solution was spin-coated on the perovskite film at 2000rpm-30s, with a thickness of about 100nm.
[0132] (5) Preparation of alloy back electrode: same as Example 4.
[0133] (6) Testing:
[0134] The test conditions are the same as those in Example 1. The obtained JV curve is as follows Fig. 9 The photovoltaic performance parameters of the cell are: open circuit voltage 1.05V, short circuit photocurrent density 20.24mA·cm -2 , the filling factor is 0.63, the photoelectric conversion efficiency is 13.50%, and the cell efficiency shows good repeatability. This shows that the In-Bi binary low melting point alloy back electrode prepared by the hot pressing method of the present invention can be used to prepare an inverted structure perovskite solar cell.
[0135] Example 6
[0136] (1) Cleaning of ITO conductive glass: Same as Example 1.
[0137] (2) Preparation of hole transport layer:
[0138] Same as Example 1, except that NiO x The layers were spin-coated on clean conductive glass substrates.
[0139] (3) Preparation of perovskite light absorbing layer: same as in Example 1.
[0140] (4) Preparation of electron transport layer:
[0141] This embodiment uses PC 61 BM+BCP (2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline) is used as the electron transport layer. PC 61 The BM layer was prepared in the same manner as in Example 5. Then, a saturated solution of BCP / isopropanol was spin-coated on the PC at 4000 rpm for 30 s. 61 On the BM layer, get PC 61 BM+BCP electron transport layer.
[0142] (5) Preparation of alloy back electrode:
[0143] This embodiment uses In-16.5Sn-32.5Bi alloy with a melting point of 60.5°C as the electrode material with a thickness of 200nm. The specific steps are the same as those in Embodiment 2, except that the applied pressure is 0.1MPa, the heating temperature is 80°C, and the holding time is 1 minute.
[0144] (6) Testing:
[0145] The test conditions are the same as those in Example 1. The obtained JV curve is as follows Fig.10 The photoelectric performance parameters of the battery are: open circuit voltage 1.06V, short circuit photocurrent density 20.93mA·cm -2 , the filling factor is 0.66, the photoelectric conversion efficiency is 14.67%, and the cell efficiency shows excellent repeatability. This shows that the In-Sn-Bi ternary low melting point alloy back electrode prepared by the hot pressing method of the present invention can be used to prepare an inverted structure perovskite solar cell.
[0146] Example 7
[0147] (1) Cleaning of ITO conductive glass: Same as Example 1.
[0148] (2) Preparation of hole transport layer:
[0149] In this example, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) self-assembled layer was used to modify NiO x As hole transport layer. NiO x The preparation of the layer was the same as in Example 6. The Me-4PACz layer modification method was as follows: 0.5 mg Me-4PACz was dispersed in 1 mL ethanol, ultrasonically dispersed, and then the dispersion was spin-coated on the NiO substrate at 4000 rpm for 30 s using a gel-spinning machine. xThe Me-4PACz modified NiO was obtained by annealing at 100℃ for 10 minutes. x Hole transport layer.
[0150] (3) Preparation of perovskite light absorbing layer:
[0151] This embodiment uses a composition of Cs 0.05 FA 0.75 MA 0.2 PbI 3 The perovskite is used as the light-absorbing layer. The specific preparation steps are as follows: 560.1 mg of lead iodide, 168.3 mg of FAI, 12.15 mg of MABr, 9.495 mg of MACl and 14.85 mg of CsI are weighed and dissolved in 0.75 mL of a mixed solution of DMF:DMSO (3:1, volume ratio), and the mixture is filtered after magnetic stirring for 12 hours for use. Before use, the solution is filtered using a 0.22 μm organic phase filter to obtain a perovskite precursor solution. The perovskite precursor solution is then spin-coated on the hole transport layer at 4000 rpm-45 s, and 200 μL of anti-solvent chlorobenzene is added in the last 15 s. After the spin coating is completed, the perovskite film is annealed at 105 ° C for 20 minutes in an environment of 30% RH to obtain a perovskite film with a thickness of about 680 nm.
[0152] (4) Preparation of electron transport layer: same as Example 6.
[0153] (5) Preparation of alloy back electrode: same as Example 4.
[0154] (6) Testing:
[0155] The test conditions are the same as those in Example 1. The obtained JV curve is as follows Fig.11 The photovoltaic performance parameters of the cell are: open circuit voltage 1.06V, short circuit photocurrent density 21.79mA·cm -2 , the filling factor is 0.79, the photoelectric conversion efficiency is 18.34%, and the cell efficiency shows excellent repeatability. This shows that by optimizing the preparation of each functional layer, a high-efficiency perovskite solar cell can be prepared by using the hot pressing method melting point alloy back electrode of the present invention.
[0156] Example 8
[0157] (1) Cleaning of ITO flexible conductive substrate:
[0158] This embodiment uses an ITO / PEN flexible conductive substrate, and its cleaning process is the same as that of Embodiment 1, except that the acetone ultrasonic cleaning step is removed.
[0159] (2) Preparation of hole transport layer:
[0160] Same as Example 1, except that NiO xThe layers were spin-coated on cleaned ITO / PEN flexible conductive substrates.
[0161] (3) Preparation of perovskite layer: same as Example 5.
[0162] (4) Preparation of electron transport layer: same as Example 6.
[0163] (5) Preparation of alloy back electrode: same as Example 6.
[0164] (6) Testing:
[0165] The test conditions are the same as those in Example 1. The obtained JV curve is as follows Fig.12 The photovoltaic performance parameters of the cell are: open circuit voltage 0.82V, short circuit photocurrent density 21.76mA·cm -2 , the filling factor is 0.57, the photoelectric conversion efficiency is 10.22%, and the cell efficiency shows good repeatability. This shows that the hot-pressed low-melting-point alloy back electrode of the present invention can be used to prepare high-efficiency flexible perovskite solar cells.
[0166] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a perovskite solar cell using a low melting point alloy back electrode, characterized in that: The steps include: (1) depositing a carrier transport layer 1, a perovskite light absorption layer, and a carrier transport layer 2 on a transparent conductive substrate in sequence to obtain a perovskite electrode; (2) laying a low melting point alloy foil flat on the carrier transport layer 2 of the perovskite electrode obtained in step (1); (3) placing a pressure mold on the alloy foil / perovskite electrode formed in step (2) to generate or apply a certain pressure; (4) heating the alloy foil / perovskite electrode in step (3) and keeping it warm for a period of time under continuous pressure, so that the alloy foil electrode is attached to the carrier transport layer 2; (5) Cooling the device described in step (4), removing the mold, and obtaining a perovskite solar cell using a low-melting-point alloy back electrode.
2. The method for preparing a perovskite solar cell using a low melting point alloy back electrode according to claim 1, characterized in that: The material of the low melting point alloy foil in step (2) is In-aSn-bBi, and the melting point selection range is 40-150°C, wherein a and b are the mass percentages of Sn and Bi in the alloy respectively, and the remainder is In; wherein 0≤a≤65, 0≤b≤90, a+b≤100.
3. The method for preparing a perovskite solar cell using a low melting point alloy back electrode according to claim 1, characterized in that: The thickness of the low melting point alloy foil in step (2) is 0.2 to 50 μm.
4. The method for preparing a perovskite solar cell using a low melting point alloy back electrode according to claim 1, characterized in that: The pressure in step (3) is 0.05-0.5 MPa.
5. The method for preparing a perovskite solar cell using a low melting point alloy back electrode according to claim 1, characterized in that: The heating temperature in step (4) is 5-20° C. above the melting point of the alloy; the insulation time is 1-20 minutes.
6. A perovskite solar cell using a low melting point alloy back electrode prepared by the preparation method according to any one of claims 1 to 5, characterized in that: It includes a transparent conductive substrate, a carrier transport layer 1, a perovskite light absorption layer, a carrier transport layer 2, and the low melting point alloy back electrode.
7. The perovskite solar cell using a low melting point alloy back electrode according to claim 6, characterized in that: The transparent conductive substrate is one of FTO conductive glass, ITO conductive glass, ITO / PET flexible substrate, and ITO / PEN flexible substrate; the perovskite light absorbing layer is Cs 1-x-y FA x MA y One of PbI3 organic-inorganic perovskite or CsPbI2Br all-inorganic perovskite, wherein 0≤x≤1, 0≤y≤1, x+y≤1, FA is a carboxamidite NH2CH=NH + , MA is methylamine CH3NH + .
8. The perovskite solar cell using a low melting point alloy back electrode according to claim 6, characterized in that: It is an upright structure battery, and the carrier transport layer 1 is an electron transport layer, which is at least one of SnO2, TiO2, and ZnO.
9. The perovskite solar cell using a low melting point alloy back electrode according to claim 6, characterized in that: The carrier transport layer 2 is a hole transport layer, which is NiO x , Spiro-OMeTAD.
10. The perovskite solar cell using a low melting point alloy back electrode according to claim 5, characterized in that: For the structured battery, the carrier transport layer 1 is a hole transport layer, which is NiO x , PTAA, PEDOT:PSS; the carrier transport layer 2 is an electron transport layer, which is one of C60 and PCBM.
Citation Information
Patent Citations
PEG-modified carbon electrode and preparation method thereof and perovskite battery prepared from PEG-modified carbon electrode
CN112614942A
Low-melting-point alloy top electrode and preparation method and application thereof
CN115867057A